International students' intention to pursue postgraduate studies in Malaysia: the moderating effect of perceived overall tourism attractiveness / Norliza Aminudin, Siti Aisyah Abd Aziz and Salamiah A Jamal - Aminudin, Norliza; Abd Aziz, Siti Aisyah; A Jamal, Salamiah (Universiti Teknologi MARA, 2023)
In recent years, international higher education and international students have attracted considerable attention in research. Using education pull factors and its perceived overall tourism attractiveness (POTA), this study aims to examine the moderating effects of POTA in influencing the behavioural intentions of current international students to continue studying in the same host country. A few studies on the pull factors of international higher education often include POTA as one of the independent variables without testing it as a moderating variable, which could enhance its importance rather than overshadow it. Data were collected from a survey of 366 international students at three higher institutions, both public and private universities, offering programmes for undergraduate and postgraduate study. Using Structural Equation Modelling (SEM), results confirmed that the pull factors influencing international students to choose the host country are language (English), quality of education, and cultural comfort. It further confirmed that POTA moderates the relationship between host country education pull factors and students’ behavioural intentions of choosing the country to further their studies. Thus, besides adding value to literature, tourism attractiveness should not be neglected and should be utilised while marketing education exports to attract international students.